Development of GeoGebra in problem-based learning to enhance students' mathematical critical thinking skills - Ade Kurniawan; Masjudin; Yuntawati; Eliska Juliangkary; Reny Amalia Permata; Syahrir; Ahmad Muzaki (Universitas Hamzanwadi, 2026)
This study is motivated by students' low critical thinking skills, particularly in three-dimensional geometry. Moreover, the limited availability of effective interactive learning media impedes the development of these skills. Three-dimensional geometry requires a more engaging and interactive approach to enhance understanding. This study aims to develop GeoGebra-based learning media within the Problem-Based Learning model to enhance students' critical thinking skills in mathematics. The research method employed is Research and Development using the ADDIE design model. The study subjects consist of eighth-grade students. The research instruments include validation sheets, practicality questionnaires, and tests. The validation results indicate that the GeoGebra validation score is reaching 95.16% (highly valid). The practicality test showed an average score of 96.09% (highly practical). The obtained N-Gain score of 0.7655 (high category) indicates an improvement in students' critical thinking abilities. The findings of this study conclude that the use of GeoGebra in PBL-based learning is effective in enhancing students' mathematical critical thinking skills and can serve as an innovative alternative for teaching three-dimensional geometry. The findings of this study have positive implications for enhancing students' critical thinking skills through the integration of interactive learning tools such as GeoGebra, which can improve engagement and understanding in mathematics.